The price of consensus. The dictatorship as portrayed in Chilean television fiction in the context of the 40th commemoration of the coup d’état - Antezana Barrios, Lorena Mónica (2017)
The extreme politicization of the field of memory was made evident by the commemoration of the 40 years of dictatorship in Chile, which was held in 2013. The different repertoires available to remember the recent past are part of the way of elaborating the past, mobilized by television in fictional formats. The stories proposed in series and mini-series, although they thematically approach the dictatorial period (1973-1989), are organized from the present. Although these stories seem to be transgressors to “show” perspectives that had been absent from television previously, they also propose a closure of meaning that reproduces “consensus”, an idea that was instilled during the transition stage to democracy.